Penerapan Metode MOORA pada Sistem Pemilihan Bibit Cabai (Kasus: Desa Bandar Siantar Kecamatan Gunung Malela) - Chairul Fadlan; Agus Perdana Windarto; Irfan Sudahri Damanik (Politeknik Negeri Batam, 2019)
Red chili is one of the plants that is often used as a complement to spices in Indonesian society and makes chili plants one of their main crops. Some farmers often find it difficult to determine which chili seeds are good and resistant to viruses. In addition, farmers are also difficult to determine good chili seeds at affordable prices. The difficulty of determining which chili seeds are good often makes some farmers fail harvests and suffer considerable losses. This research was conducted in the village of Bandar Siantar, Gunung Malela District. Data is obtained by interviewing and observing directly to chili farmers. This study uses a decision support system technique with the Multi-Objective Optimization method on the basis of Ratio Analysis (MOORA) which can help farmers to determine good chili seeds. The assessment criteria used were the price of seeds (C1), Harvest Period (C2), Fruit Length (C3), Fruit Weight (C4), Chili Disease (C5), Number of Branches (C6) with 8 alternatives, namely: Lado (A1), Taro (A2), Belinda (A3), TM (A4), Kripsy (A5), Tebing (A6), Indra Pura (A7) and Keling (A8). The results of applying the MOORA method in choosing chili seeds are the type of Lado (A1) chili with a value (Yi (max) = 0.2080) becomes the first recommendation, TM (A4) with a value (Yi (max) = 0.2071) being ranked second and Indra Pura (A7) with a value (Yi (max) = 0.1974) becomes third place. This research is expected to help farmers in determining good chili seeds so that they can help the economy of the farmers and avoid crop failure, especially in the village of Bandar Siantar, Gunung Malela District.